CELLULOSIC MEMBRANES SUPPORTED WITH SILICA FROM RICE HUSK AND RICE HUSK ASH FOR SLOW RELEASE - Francine Gastaldon; Eduardo Junca; Felipe Fardin Grillo; Antônio Carlos Sobieranski; Suzane Quintana Gomes; Jamal Rafique; Tatiana Gisset Pineda Vásquez; Tiago Elias Allievi Frizon (Química Nova)
The aim of this work was to study silica extraction from rice husk (RH) and rice husk ash (RHA). Bacterial cellulose (BC) was used to transport the extracted silica as well as the slow-release silica material. The silica extraction from RH and RHA was performed by leaching using ultrapure water and NaOH. Silica was quantified by UV-Vis spectrophotometer. BC membranes were produced with Komagataeibacter hansenii. Then, the membranes were impregnated with silica-rich leached extracts. Silica release tests under controlled conditions were conducted. Characterization of the impregnated membranes was conducted by Fourier transformed infrared spectrometry (FTIR), microstructural (scanning electron microscopy (SEM)) and mechanical resistance analyses. The results indicated that the RH and RHA leachates from the extractor solution containing NaOH contained more silica than did the extracts from ultrapure water. The BC membranes supported with the aqueous extract of RH released 58% of the adsorbed silica in 24 h. The BC membranes impregnated with RHA-H2O released 67% of the silica. The silica release reached 62% for RH and 60% for RHA from the extract leached with NaOH. The membranes showed a high capacity to retain both water and silica, which can be an alternative to reduce economic losses due to solubilization of fertilizers in the agricultural sector.